The Application of Sharia Maqashid on the Protection of the Rights of Minority of Muslim Rohingya in Regional ASEAN (Indonesia-Malaysia) - Towadi, Mellisa (Universitas Negeri Semarang, 2017)
This study aims, first, to analyze the application of the principles of Maqashid Sharia as a principle of human rights protection against the Rohingya Muslim minority. Second, assess the extent of regional efforts (ASEAN) to protect the Rohingya Muslim minority is based on the principles of Maqashid Sharia. This study is normative juridical, i.e basic research study is conceived as legal norms or rules which apply, both contained Islamic Law and International Law. Further, legal materials collected in the process were analyzed based approach to the law (statute approach) and qualitative approach. The results showed, first, the principle of Maqashid sharia are the fundamental principles that are in line with international human rights principles set forth in the Universal Declaration Human Rights of 1948, the ASEAN Charter and the international conventions that have been globally accepted. Its application carries its own moral responsibility for the ASEAN region, to encourage its member countries (particularly Indonesia and Malaysia) obligations responsibility to protect (R2P) to the ethnic Rohingya. When referring to the ASEAN charter alone, especially member states Indonesia and Malaysia will be very limited in giving aid directly to the territory of the Rohingya, given in addition to avoiding any intervention factor that arises, as well as the government of Myanmar has declared the anti-Islamic rule in the territories of its constitution. This is the regional challenges, especially for Indonesia and Malaysia as member states that embrace the principles of Islamic law once the state of the organization with Myanmar. Secondly, efforts should be made Indonesia and Malaysia are fulfilling rights Rohingya people merely when they became refugees or asylum seeker in the country. The rights can be met as a complement of the principle maqashid sharia, among others: a) freedom of religion, the right to life and freedom from fear (maintenance of soul) in this case Indonesia has established the Integrated Community Shelter (ICS) as a residence of Rohingya refugees and build mosques or places worship for Muslims Rohingya named mosque Arakan, b) fulfill the safety assurance, guarantee of human dignity (maintenance of breath), c) custody of ethnic or tribal, the right to marriage to the breeding (maintenance of descent), d) the right to education (maintenance sense), e) the right to receive a decent living by being given the opportunity to earn a living (maintenance of property).